Análise transcriptômica de pedúnculos de caju (Anacardium occidentale L.) durante o desenvolvimento em genótipos apresentando cores e firmezas diferentes - Germano, Thais Andrade (2020)
The cashew apple Anacardium occidentale L.) has great economic and social importance worldwide, due to its high nutritional value, in addition to its peculiar flavor and aroma During its maturation , the peduncle shows a fast fi rm n ess redu c t ion and d evelopment of different peel coloration , impacting the quality and acceptance of pseudofruit by consumers. Although many studies discuss ab out the firmness and color of the peduncle s, the m olecular mechan isms involv ed in the alterations of t h ese char acte ristics during cashew development are still unknown. Therefore, the aim of this study was to analyze the peduncle transcriptome of two cashew a pple genotypes (CCP 76 and BRS 265) with differe nt firmness and color in two development al s tages (immature and mature), using the RNA Seq technique ( RNA sequencing ). F rom the results it was possible to observe reduced firmness and anthocyanin content in the peduncles during the development of both gen otypes. However, the immature and mature BRS 265 cashe w apple s showed greater firmness and higher anthocyanin conten t than CCP 76 cashew apple s at the same maturation stages. Differential expression analysis revealed a total of 3,266 differentially express ed genes ( DEG s) between immature and mature BRS 265 cashew apple s , while between immature and mature CCP 76 cashew apples , 4,374 DEG s were identified. Subs equently, the functional enrichment analysis of DEG s showed that the genotypes showed responses, main ly, to the softening process (catabolism and biogenesis of cell wall macromolecules ) and development peel coloration flavonoids and phenylalanine biosynthe sis ) of the peduncles. A total of 71 and 34 DEG s involved in the softening process and flavonoid bio synthesis were identified in cashew apple peduncle , respectively. In general, firmness difference between the studied genotypes cou ld be justified by the down regulation of genes encoding expansin (EXP), as well as by the up regulation of genes encoding en zymes involved in the pectin degradation [polygalacturonase (PG), pectatoliase (PL ) and pectin acetyltransferase (PAE )] and cell wall biosynthesis in CCP 76 cashew apple (softer peduncle ). The red coloration peel and high anthocyanin content in immature BR S 265 cashew apple could be associated with the up regulation of genes encoding enz ymes involved in the flavonoid biosynthesis [phenylalanine ammonia lyase (PAL), cinnamate 4 hydroxylase ( and chalcone synthase (CHS)] compared to CCP 76 cashew apple at the same developmental stage . Finally, six DEG s involved in the metabolisms of inte rest in this study (firmness and flavonoids) had their transcriptional pattern validated by real time polymerase chain reaction (RT qPCR). The information from this study m ay provide subsidies for future research, aiming at extending post harvest life, as well as the quality of cashew apple